POLITICAL COMMUNICATION AND THE ROLE OF TERRITORIAL COMMANDERS IN NIGERIA: IMPLICATIONS FOR COHESION, GOVERNANCE AND FUTURE SUÇCESS - Otuogha, Austin Mathias; Eke, Chigozi; Amalagha, William Inamuna (International Journal of Political Science and International Relations (IJPSIR), 2025)
This study analyzed political communication and the role of Nigerian territorial commanders: implications for cohesion, governance and future success. Agenda setting theory formed the anchor for this research. A qualitative research design with email interviews was used as the main data collection approach in analyzing the communicative roles of Nigeria's territorial commanders and their implications for governance and national cohesion. The population of concern was the territorial commanders of the Nigerian Armed Forces, public affairs officers, and a representative sample of civil society actors and policy analysts tracking civil-military relations totaling over 1,200 people from Nigeria's six geopolitical zones. Purposive sampling was employed to select a sample of 20 participants that including 10 territorial commanders, 5 media/public affairs officers, and 5 civil society actors. Participants responded to semi-structured interview questions were filled out and returned online through email to enable them to respond conveniently without losing the depth and adaptability required in qualitative research. Thematic analysis was used to examine the recurring patterns, meaning and contrasts in the responses. The research revealed that Nigeria's operational commanders utilize limited and strategic modes of communication, such as press conferences, social media discussions and local community talk in order to control public image, counter misinformation and augment security goals in addition to offsetting operation secrecy. The research found that strategic and controlled communication behavior by territorial commanders is essential in managing security narratives and public opinion, enhancing the ability of the military’s ability to be secretive when interacting with diverse audiences. The research advised the Nigerian Defense Headquarters that it should provide assurance that territorial commanders embrace uniformity and open communication behaviors to construct public awareness and trust.